Biomass Burning in Southeast Asia and Influences on Atmospheric Nanoparticles - Racha Dejchanchaiwong; Perapong Tekasakul; John Morris; Thammasin Ingviya; Mohd Talib Latif; Norhaniza Amil; Mitsuhiko Hata; Masami Furuuchi; Doreena Dominick; Rachane Malinee (My University, 2022)
Rapid economic growth has led to increasing air pollution in Southeast Asia (SEA). Urbanization, industrialization and open biomass burning all lead to deteriorating air quality. Recent advances allow recording, sampling and analyzing ultrafine particles, or nanoparticles, finer than the already extensively reported PM2.5 particles; these nanoparticles have been shown to be a potentially more significant health hazard – causing cardiovascular and respiratory diseases, since they can penetrate further into our bodies. Analysis of the collected particles allows, in turn, identifying sources. Although vehicle emissions generally dominate nanoparticles, biomass generates a significant proportion in the burning seasons. In Malaysia, the number of particles smaller than 50 nm dominate, but, by mass, PM0.1 accounts for ∼15% of PM2.5 in upper SEA, and ∼18% in lower SEA. Sampling compared normal periods, where ratios of organic to elemental carbon and char to soot elemental carbon indicated that vehicle exhaust dominates. However, in haze periods, increased char to soot elemental carbon ratios indicate strong contributions from biomass burning. In lower SEA severe haze periods, polycyclic aromatic hydrocarbon levels are 3–8 times higher than in normal periods, confirming the sources as peatland fires in Indonesia. Open biomass burning clearly contributes a significant portion of PM0.1 during SEA haze periods. Further PM0.1 studies are needed to better understand sources, transport and influences on human health to identify suitable measures to solve the problem sustainably.
Keywords: Air Quality and Health Impacts; Atmospheric chemistry and aerosols; Energy and Environment Impacts